Characterisation of eppin function: expression and activity in the lung. Issue 1 (13th July 2017) - Scott, Aaron; Glasgow, Arlene; Small, Donna; Carlile, Simon; McCrudden, Maelíosa; McLean, Denise; Brown, Ryan; Doherty, Declan; Lundy, Fionnuala T.; Hamid, Umar I.; O'Kane, Cecilia M.; McAuley, Daniel F.; et al.
Eppin is a serine protease inhibitor expressed in male reproductive tissues. The aim of this study was to investigate the localisation and regulation of eppin expression in myeloid and epithelial cell lines, and explore its potential role as a multifunctional host defence protein. Using immunohistochemistry and Western blotting, eppin was detected in the lungs of patients with acute respiratory distress syndrome and cystic fibrosis lung disease. Expression of eppin in monocytic cells was unaffected by stimulation with Toll-like receptor agonists, cytokines and hormone receptor agonists. However, upregulated expression and secretion of eppin was observed following treatment of monocytes with epidermal growth factor. Incubation of recombinant eppin with monocytic cells resulted in significant inhibition of lipopolysaccharide-induced chemokine production. Furthermore, eppin inhibited lipopolysaccharide-induced NF-κB activation by a mechanism which involved accumulation of phosphorylated IκBα. In an in vivo model of lung inflammation induced by lipopolysaccharide, eppin administration resulted in decreased recruitment of neutrophils to the lung with a concomitant reduction in the levels of the neutrophil chemokine macrophage inflammatory protein-2. Overall, these results suggest a role for eppin outside of the reproductive tract and that eppin may have a role in the innate immune response in the lung. Eppin is a low-molecular-weight protein which is expressed in the human lung during inflammation http://ow.ly/WZuQ30aELEI